Developing Stakeholder Theory - Friedman, Andrew L.; Miles, Samantha (Journal of Management Studies, 2002)
Previous literature has led to a lack of appreciation of: the range of organization/stakeholder relations that can occur; the extent to which such relations change over time; as well as how and why such changes occur. In particular, extremely negative and highly conflicting relations between organizations and stakeholders have been ignored. Due to this lack of appreciation it is argued that current attempts at integrating the separate strands of stakeholder theory to achieve a convergent stakeholder theory are premature. A model is presented which combines stakeholder theory with a realist theory of social change and differentiation. This model is intended to highlight why it is important to distinguish different stakeholders. The model also enables an analysis of the organization/stakeholder relationship, which is not exclusively from the organization perspective and which is capable of illuminating why and how organization/stakeholder relations change over time. The history of Greenpeace is used as an example.